Analysis of The Influence of System Quality, Information Quality, Service Quality on Net Benefits in The Finance Billing Management System (FBMS) - Ayu Selia Maharani; Indra Lukmana Putra (Journal of Applied Accounting and Taxation, 2024)
The information system applied at BP Batam is the Finance Billing Management System (FBMS). FBMS manages financial reports from budgeting, receipts, and expenditures. This study examines how the quality of the system, information, and service influence user satisfaction and how user satisfaction impacts the net benefits of implementing the FBMS application at BP Batam. This research model adopts the DeLone and McLean IS success model. This research uses quantitative research. The population in this study were employees of BP Batam with a sampling technique using a nonprobability sampling method. The sample used was 60 FBMS users. The findings indicate that user satisfaction is influenced by system, information, and service quality, which in turn influences net benefit.